Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d0tb02366c
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal effect and cytotoxicity of CuS nanoflowers deposited over folic acid conjugated nanographene oxide

Abstract: Herein, we present the rational synthesis of a multimode photothermal agent, NGO–FA–CuS, for the advancement of photothermal therapy of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In addition, 1694 cm −1 peak (C=O stretching vibration) of FA was free carbonyl group, but this peak shifted to 1638 cm −1 (C=O stretching vibration of amide peak (I)) of FA-modified siRNA/PEI@PDA. And FA-modified siRNA/PEI@PDA also had characteristic amide NH peak (II) at 1534 cm −1 , indicating FA was successfully modified on the surface of PDA nanomedicine [ 35 , 36 ]. The particle size and zeta potential of the siRNA/PEI NPs, siRNA/PEI-loaded PDA nanomedicine and FA-modified siRNA/PEI-loaded PDA nanomedicine were also measured.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 1694 cm −1 peak (C=O stretching vibration) of FA was free carbonyl group, but this peak shifted to 1638 cm −1 (C=O stretching vibration of amide peak (I)) of FA-modified siRNA/PEI@PDA. And FA-modified siRNA/PEI@PDA also had characteristic amide NH peak (II) at 1534 cm −1 , indicating FA was successfully modified on the surface of PDA nanomedicine [ 35 , 36 ]. The particle size and zeta potential of the siRNA/PEI NPs, siRNA/PEI-loaded PDA nanomedicine and FA-modified siRNA/PEI-loaded PDA nanomedicine were also measured.…”
Section: Resultsmentioning
confidence: 99%
“…208 Third, only when the size of the photothermal agent is small enough can it enter the tissue cells for photothermal therapy, so it must have superior tissue targeting. 209 At present, widely used photothermal materials include noble metal nanoparticles such as Au, Ag and Pt, 210,211 carbon materials such as graphene and carbon nanorods, 212 metal and nonmetal compounds such as CuS and ZnS, 213 and organic dyes such as indocyanine green and Prussian blue, 214 while few studies have mentioned CQDs. CuS nanoparticles carrying CQDs and bortezomib were synthetized, coated with macrophage membranes and modified with the T7 peptide to form CuSCDB@MMT7.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…As a plasmonic material, it absorbs near-infrared (NIR) light and converts it into heat due to d-d transition of copper ion and non-radiative relaxation [ 17 ]. The broad absorption in the NIR region has made Cu 2-x S, such as CuS, Cu 2 S, and Cu 7 S 4 , great candidates in the photothermal field [ 18 , 19 , 20 ]. For instance, researchers have found that under irradiation of 980 nm, modified-CuS nanoflowers were able to attain a temperature of 63.1 °C within 5 min [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The broad absorption in the NIR region has made Cu 2-x S, such as CuS, Cu 2 S, and Cu 7 S 4 , great candidates in the photothermal field [ 18 , 19 , 20 ]. For instance, researchers have found that under irradiation of 980 nm, modified-CuS nanoflowers were able to attain a temperature of 63.1 °C within 5 min [ 18 ]. In particular, Cu 2 S has the features of low cost, abundance, recyclability, low toxicity, good stability, and intrinsic plasmonic properties [ 21 ], leading to uses in the fields of electronics, optoelectronics, photoelectrochemicals, biosensors, and photothermal materials.…”
Section: Introductionmentioning
confidence: 99%